Myelomeningocele a congenital disease in Chiapas - Aceituno Ovando, Grace; Jiménez Ocaña, María Rosalba (Revista Anales de Medicina Universitaria, 2023)
Introduction: Neural tube defects (NTDs) are congenital defects of the central nervous system, the result of inadequate closure in some area of the neural tube, such as Spina Bifida, Anencephaly or Myelomeningocele (MMC), which are a group of conditions that occur during the embryological period of the human being. preventable and greatly affect the population. In Latin America and Mexico they are among the main causes of infant morbidity and mortality. Material and Methods: Analysis of data series of newborns with NTDs in Tuxtla Gutiérrez Chiapas, Mexico from 2021-2023 generated from the data and evidence collected at the Dr. Rafael Pascacio Gamboa Regional Hospital and with information from the Tube Defects Epidemiological Surveillance System Neural and Craniofacial (SINAVE/DGE/Salud/2020.). 4 cases with NTDs were included, specifically Myelomeningocele who were born and reside in the State. The annual rates of cases with NTDs were exposed to identify possible factors that affect or increase said affections with the purpose of preventing said defects or, in that case, ensuring optimal secondary and tertiary prevention for the life of the affected individuals. Results: In the period studied, which was 2021-2023, the NTDs with the highest incidence was MMC with 4 cases generated with diseases associated with hydrocephalus and microcephaly, of which only 10% of the cases consumed folic acid in a timely manner during the first trimester. of pregnancy. 100% of the cases are low-income and do not have higher education, as well as popular insurance. 90% attended 6 prenatal consultations or less. Conclusions: NTDs are one of the most frequent problems in newborns, they require study, treatment and permanent surveillance, they can be treated with therapies or go as far as immobilization of the patient's upper and lower limbs, and even death. They represent with great force a morbidity and mortality in childhood that affects the individuals who suffer from them, these conditions are very difficult to bear in the economic, neurological, behavioral, social, emotional, psychological and physical aspect of the people who suffer from it and suffer as much as the affected individuals as well as their families, friends, society, and the health system. Especially because it is preventable, and the information on how to avoid it is of vital use in family planning and to provide more data on this group of diseases where there are more and more new data, methods and techniques on what they are and how to avoid them, cope with them with the purpose of reducing its incidence in the mexican and general population around the world.